Influência dos diferentes tratamentos térmicos a 900°C nas variações microestruturais produzidas no Aço SAE 4320 - Anastácio, Andrey Pompeu (2020)
SAE 4320 steel is widely used in the manufacture of gears, pinions, pins and machine components, where there is a requirement for surface hardness, obtained by the case-hardening process, as it is a high-strength, low-alloy steel (ARBL). It is considered a micro-alloyed steel, that is, with low compositions of alloy elements that mostly confer the desired mechanical properties, enabling its importance for the aforementioned applications. It has good forging and weldability, as well as high hardenability, toughness, but poor machinability. It is a steel linked to chromium (Cr), nickel (Ni)), molybdenum (Mo) and carbon (C), as main elements, among others, which will be mentioned later. The low carbon content allows the use of the carburizing thermochemical treatment to increase wear resistance. This research aims to analyze and investigate the microstructure, as well as the mechanical properties of SAE 4320 steel in view of the different heat treatments carried out at 900 o C. In this perspective, as the thermal treatments were being carried out, the appearance of phases and diverse micro constituents, for example, in the heat treatments of quenching the appearance of the martensite phase that presents high hardness in comparison to other phases. In addition, in the heat treatment of quenching in water followed by tempering, a change in the morphology of the martensitic phase and a drop in hardness were observed at the expense of reasons that will be addressed later. In addition, in the heat treatment of oil quenching, a plurality of phases occurred due to the insufficient heating time. With that, the expected martensite phase was verified. In addition, a certain amount of austenite retained. Finally, in the annealing and normalization heat treatments, a predominance of ferritic and pearlitic micro constituents was noticed. Thus, through usual metallographic sample preparation techniques, as well as through hardness tests, chemical analysis, optical microscopy and scanning electron microscopy (SEM), it was possible to make an analysis of the microstructural variation of the steel under study.